2017
DOI: 10.1021/acs.joc.7b00822
|View full text |Cite
|
Sign up to set email alerts
|

Initiation in Photoredox C–H Functionalization Reactions. Is Dimsyl Anion a Key Ingredient?

Abstract: Previous studies have reported the arylation of unactivated arenes with ArX, base (KOBu or NaOBu), and an organic additive at high temperatures. Recently, we showed that this reaction proceeds in the absence of additives at rt but employs UV-vis light. However, details of mechanisms that can use a photoinduced base-promoted homolytic aromatic substitution reaction (photo-BHAS) have remained elusive until now. This work examines different mechanistic routes of the essential electron-transfer step (ET) of this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 79 publications
1
30
0
1
Order By: Relevance
“…In the absence of further additives, it has recently been shown that the dimsyl anion can be excited by visible light and plays a pivotal role in initiating the reaction (see Scheme 46). [135] The initiation of the BHAS reaction was also reported by other photoactivation modes, for example, through PET from an iridium sensitizer to R‐X, or upon excitation with light of an in situ formed photosensitive complex between KO t Bu and phenanthroline [136, 137] . Non‐nucleophilic bases are commonly employed to avoid the competing S RN 1 reaction pathway.…”
Section: Excited Anionic Compounds As Reagentsmentioning
confidence: 94%
“…In the absence of further additives, it has recently been shown that the dimsyl anion can be excited by visible light and plays a pivotal role in initiating the reaction (see Scheme 46). [135] The initiation of the BHAS reaction was also reported by other photoactivation modes, for example, through PET from an iridium sensitizer to R‐X, or upon excitation with light of an in situ formed photosensitive complex between KO t Bu and phenanthroline [136, 137] . Non‐nucleophilic bases are commonly employed to avoid the competing S RN 1 reaction pathway.…”
Section: Excited Anionic Compounds As Reagentsmentioning
confidence: 94%
“…The experiments discussed above reflect ground-state chemistry, but the situation may be different and even more extensive for excited-state reactions. Rossi et al have been chief proponents of the use of light in BHAS-type coupling reactions, particularly in the presence of DMSO, 46,47 and several authors have proposed that a DMSO anion may be the electron donor in certain reactions [48][49][50] In relation to phenanthroline, Yuan et al showed 51 that besides thermal activations, visible light can be used effectively to generate electron donor species by direct reaction of phenanthrolines with KOtBu within a complex. Similarly, Nocera et al 52 showed that visible light promoted direct electron transfer from KOtBu to benzophenone to form the corresponding blue potassium ketyl, a known strong electron donor.…”
Section: Short Review Syn Thesismentioning
confidence: 99%
“…To address the challenges, we envisioned that a controlled radical-mediated reaction could afford a high activity and selectivity because the rearrangement of reactive carbon-centered radicals is significantly slower than that of their cationic counterparts 23 . Although homolytic aromatic substitution (HAS), the radical analog of the electrophilic aromatic substitution, has been well developed 24 , 25 , the insertion of nucleophilic alkyl radicals to the electron-rich π-system of arenes is significantly more sluggish and the alkyl radicals are prone to undergo side reactions, such as homodimerization and hydrogen atom transfer (HAT) 23 , 26 , 27 . To control the reaction pathways, the recently reported photoinduced Pd catalysis approach was identified as an attractive activation mode to generate alkyl radicals from alkyl halides, since it operates under mild conditions while controlling the concentration of free radical species to suppress undesired side reactions 16 , 19 , 28 36 .…”
Section: Introductionmentioning
confidence: 99%